Quality of CT Scan Service to Patient Satisfaction in Radiology Unit of “Harapan Keluarga” Hospital - Kendra Wardhani Khrisnawathy (Health Notions, 2018)
The CT scan inspection data from the Radiology unit at Harapan Keluarga hospital showed a decrease in the number of visits in 2014, is 457 patients with a target of 550 patients. The purpose of this study is to provide an overview of the quality of CT scan services on the level of patient satisfaction. This research used descriptive survey method. This research was conducted from November to December 2015 in Radiology Unit of Harapan Keluarga Hospital of Mataram City. Sample size in this study was 93 patients in period of 2012-2014, selected by using purposive sampling. Data collection method used is questionnaire or questionnaire. Primary data obtained through interviews or filling questionnaires given to respondents. The result showed that the quality of service to patient satisfaction CT scan from aspect tangible good service (86.0) good service reliability (64.5%), good service assurance (74.2%), good service responsiveness (61.3%) and good service empathy (50.5 %). Can be concluded based on patient satisfaction items that CT scan service has good category. The need to make the rules/SOP of CT scan patients concerning alertness and awareness of officers to be available if needed patients, conduct socialization to provide information about the program of promotional activities in patients. Keywords: satisfaction; quality service; CT scan; inspection